Formulation Development of Mucoadhesive Microparticle-Laden Gels for Oral Mucositis: An In Vitro and In Vivo Study - Hiroomi Sakurai; Yuri Ikeuchi-Takahashi; Ayaka Kobayashi; Nobuyoshi Yoshimura; Chizuko Ishihara; Tohru Aomori; Hiraku Onishi (MDPI AG, 2020)
In order to relieve pain due to oral mucositis, we attempted to develop mucoadhesive microparticles containing indomethacin (IM) and gel preparations with IM microparticles that can be applied to the oral cavity. The mucoadhesive microparticles were prepared with a simple composition consisting of IM and polyvinyl alcohol (PVA). Two kinds of PVA with different block properties were used, and microparticles were prepared by heating-filtration and mixing-drying. From the X-ray powder diffraction patterns, differential scanning calorimetry thermograms, and morphological features of the IM microparticles, IM should exist as polymorphic forms in the microparticles. Rapid drug release properties were observed in the IM microparticles. Increased drug retention was observed in IM microparticles containing PVA, and the IM-NK(50) gel, using a common block character PVA and heating-filtration, showed good long-term drug retention properties. In vivo experiments showing significantly higher drug concentrations in the oral mucosa were observed with IM microparticles prepared by heating-filtration, and the IM-NK(50) gel maintained significantly higher drug concentrations in the oral mucosa. From these results, the IM-NK(50) gel may be useful as a preparation for relieving oral mucositis pain.